(untitled) (Al-Qamar, 2020)
Said Nursi learned the Holy Qur’an and its lessons deeply which invites the learner to research in the natural phenomena. He believed that Qur’an describes not only the principles for rise of a nation but also its economic and technological development. He claimed the fall of Ummah is the drawback of denying the guidelines of Qur’an for a successful nation. On the basis of Qur’anic interpretations, he quoted eight major causes of turmoil for Muslim world and gave their explanations. The heart of this movement was to realize people for unity of Muslim world, consultation and to follow the divine instructions to get rid of problems of Muslims.